2014
DOI: 10.5946/ce.2014.47.6.478
|View full text |Cite
|
Sign up to set email alerts
|

Prevention Strategies for Gastric Cancer: A Global Perspective

Abstract: Despite the substantial burden of gastric cancer worldwide, population strategies for primary prevention have not been introduced in any country. Recognizing the causal role of Helicobacter pylori infection, there is increasing interest in population-based programs to eradicate the infection to prevent gastric cancer. Nonetheless, the paucity of available evidence on feasibility and effectiveness has prevented implementation of this approach. There are very few secondary prevention programs based on screening … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
93
0
8

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(103 citation statements)
references
References 81 publications
2
93
0
8
Order By: Relevance
“…Globally, gastric and gastroesophageal junction (GEJ) cancers are the second leading cause of death. The highest incidence of gastric/GEJ cancers is observed in Eastern Asia, Central and Eastern Europe, and South America 2, 3…”
Section: Epidemiology Of Gastric Cancermentioning
confidence: 99%
“…Globally, gastric and gastroesophageal junction (GEJ) cancers are the second leading cause of death. The highest incidence of gastric/GEJ cancers is observed in Eastern Asia, Central and Eastern Europe, and South America 2, 3…”
Section: Epidemiology Of Gastric Cancermentioning
confidence: 99%
“…They found that people of highest income are less likely to have UGI treatment (OR = 0.93, 95 % CI 0.64-1.35) and more likely to have endoscopy (OR = 1.42, 95 % CI 1.07-1.89) compared to the lowest income group. Several previous studies also describe an association between income and stage of gastric cancer when diagnosed [28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…Las mayores tasas se observan entre las regiones del Maule y Aysén 1 . Además, se ha descrito una mayor mortalidad por esta enfermedad a menor nivel socioeconómico 3,4 .…”
unclassified